A new genus and a new species of the tribe Mithymnini (Hemiptera: Fulgoromorpha: Nogodinidae) from Namibia, with sternal sensory pits in the adult - Gnezdilov, Vladimir M.; Wilson, Michael R. (Zootaxa, 2007)
A new genus and a new species of the tribe Mithymnini – Fovealvus nama sp. nov. is described from Namibia. Fovealvus gen. nov. differs from all other genera of the tribe due to the presence of large sensory pits on VI and VII abdominal sternites in the adult.